Impact of GLP-1 Receptor Agonists on Body Composition and Physical Performance in Patients with Obesity: A Comprehensive Review of Current Research - Turczynowski, Konrad; Lichoń , Jakub; Kuna , Paweł; Turczynowski, Kamil; Kuna , Wojciech; Pietrucha, Jakub; Gołdyn, Mateusz; Niski , Jakub; Rutkowska, Anna; Studziński, Dawid (Quality in Sport, 2026)
Background. GLP-1 receptor agonists (GLP-1RAs) are central to obesity pharmacotherapy, producing substantial and sustained weight loss in randomized trials, with additional cardiometabolic benefits. Growing attention concerns their effects on body composition, particularly fat versus lean mass loss, and potential impacts on skeletal muscle function and physical performance. These outcomes are highly relevant to sports medicine and rehabilitation, where muscle preservation is crucial. Aim. To review evidence on the effects of GLP-1RAs on body composition and physical performance in adults with obesity, focusing on fat mass, lean mass and populations at risk of muscle-related adverse effects. Materials and methods. Narrative review of 30 PubMed-indexed studies (2015–2026), including RCTs, DXA substudies and reviews of liraglutide, semaglutide and tirzepatide in adults with overweight/obesity. Results. GLP-1RAs consistently reduced body weight and fat mass, with 15–40% of weight loss attributable to lean mass reduction. Semaglutide improved physical function and exercise tolerance in obesity-related functional impairment and HFpEF, while potential sarcopenic effects were reported in older adults and those with low baseline muscle mass. Reviews highlight heterogeneity of lean mass responses and the importance of lifestyle interventions. Conclusions. GLP-1RAs induce major fat loss but are associated with clinically relevant lean mass loss. Combining pharmacotherapy with exercise and nutrition is essential to optimize body composition and physical performance.